Application of portable FTIR spectrometers for detecting greenhouse gas emissions of the major city Berlin - F. Hase (Atmospheric Measurement Techniques, 2015)
Five portable Bruker EM27/SUN FTIR (Fourier transform infrared) spectrometers have been used for the accurate and precise observation of column-averaged abundances of CO2 and CH4 around the major city Berlin. In the work by Frey et al. (2015), a calibration procedure is developed and applied to the set of spectrometers used for the Berlin campaign. Here, we describe the observational setup of the campaign and aspects of the data analysis, and we present the recorded time series of XCH4 and XCO2. We demonstrate that the CO2 emissions of Berlin can be clearly identified in the observations. A simple dispersion model is applied which indicates a total strength of the Berlin source of about 0.8 t CO2 s−1. In the Supplement of this work, we provide the measured data set and auxiliary data. We hope that the model community will exploit this unique data set for state-of-the art inversion studies of CO2 and CH4 sources in the Berlin area.